2014
DOI: 10.1159/000362093
|View full text |Cite
|
Sign up to set email alerts
|

Infrastructure and Facilities for Human Biobanking in Low- and Middle-Income Countries: A Situation Analysis

Abstract: Objective: To collect information on biobanking facilities in low- and middle-income countries (LMICs) as a first step towards establishing an LMIC biobank and cohort building network (BCNet) to support research, with a focus on cancer control. Method: Sixty centres were identified from sources including cancer centres, universities, hospitals, and public health facilities and invited to participate in a survey between December 2012 and March 2013. Results: Of the 27 centres (45%) that responded, most have exi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
30
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 46 publications
(30 citation statements)
references
References 30 publications
0
30
0
Order By: Relevance
“…The surveys among biobanks operating in a LMIC environment show that biobanks have so far mainly been created to support specific programmes targeting major health issues in the countries hosting the biobank [4]. Such programmes may be successful in achieving their aims and also set a precedent for effective biobank management in the region.…”
Section: Maximizing the Social And Economic Impact Of Biobanks In Africamentioning
confidence: 99%
See 1 more Smart Citation
“…The surveys among biobanks operating in a LMIC environment show that biobanks have so far mainly been created to support specific programmes targeting major health issues in the countries hosting the biobank [4]. Such programmes may be successful in achieving their aims and also set a precedent for effective biobank management in the region.…”
Section: Maximizing the Social And Economic Impact Of Biobanks In Africamentioning
confidence: 99%
“…Results from the survey showed that, although information on biobanking activities in Africa is limited, biological resource management infrastructure is being developed [4]. Biobanks were introduced through specific programmes targeted at major health issues affecting the populations of these countries (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…9,10 African populations are genetically diverse. Fully understanding the genetic basis of disease among the different populations, geographically and ethnically, is central to improving healthcare by identifying new targets for diagnosis and therapy.…”
mentioning
confidence: 99%
“…Ownership of the research generated will ensure that findings translate into healthcare practices in the local community, health policies, and regulations. 10 Storage of biological material from patients with rare diseases, found only in African populations, in addition to large stores of material from patients with common conditions, which pose a significant public health risk, and from healthy controls 5,15 will enable Africans to participate in global initiatives to counter health threats.…”
mentioning
confidence: 99%
“…Thus, in the first paper, Monaco and Crimi [1], describe the challenges posed by networks of biobanks across different regions and countries in Europe, based on the paradigm of biobanks for rare diseases and the RD-Connect European project. In the subsequent articles, Ravid [2] describes the uniqueness of biobanks of neurological tissues based on the experience of the Netherlands BrainBank, whereas Mackenzie [3] compares and discusses the differences in biobanking for the pharma and biotech industry versus academic research, and Mendy et al [4] review the situation of biobanks in low- to middle-income countries.…”
mentioning
confidence: 99%